2019
DOI: 10.1111/jen.12640
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation of wild native box trees (Buxus sempervirens): Does box rust (Puccinia buxi) infection influence herbivory, survival and growth of the invasive Cydalima perspectalis?

Abstract: The invasive box‐tree moth Cydalima perspectalis causes damage to horticultural box trees (Buxus spp.) in private gardens and parks in Europe and defoliation of large areas of European native box trees Buxus sempervirens, which grow in the understorey of deciduous forests. In some parts of their distribution area, wild native box trees are infected by the box rust Puccinia buxi, a fungus which does not occur in the native range of C. perspectalis. We examined whether the infection of P. buxi deters grazing by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In areas with higher altitudes than those in this study, decreased temperatures in July or August will limit the larval population by increasing the diapause induction of the offspring of the first generation of adults. This first generation will depend on winter mortality factors affecting the diapausing larvae, little known so far as could be entomopathogenic fungi‐ or plant‐associated microorganisms (Baur et al, ). The survival of natural boxwood in the studied area will depend on its ability to regrow one to two years after defoliation and on the adaptation of several indigenous natural enemies of the region to feed on C. perspectalis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas with higher altitudes than those in this study, decreased temperatures in July or August will limit the larval population by increasing the diapause induction of the offspring of the first generation of adults. This first generation will depend on winter mortality factors affecting the diapausing larvae, little known so far as could be entomopathogenic fungi‐ or plant‐associated microorganisms (Baur et al, ). The survival of natural boxwood in the studied area will depend on its ability to regrow one to two years after defoliation and on the adaptation of several indigenous natural enemies of the region to feed on C. perspectalis .…”
Section: Discussionmentioning
confidence: 99%
“…Zamani, Farahani, Farashiani, Salehi, and Samavat () found larvae infected by Beauveria bassiana (Balsamo) in Iran. Recently, Baur, Jung, and Rusterholz () found that the performance of the C, perspectalis larvae decreased when they fed on box leaves infected with the box rust, Puccinia buxi (DC). Finally, Peterlin, Rodic, and Trdan () mention predation by birds in Slovenia.…”
Section: Introductionmentioning
confidence: 99%
“…Even if prior herbivory induced the production of chemical defenses, it is possible that this did not exert any particular pressure upon females for choosing undefended leaves or plants on which to oviposit, as their offspring would have been able to cope with it. Last, BTM larvae proved to be unable to distinguish between box tree leaves infected or not by the box rust Puccinia buxi, while their growth is reduced in the presence of the pathogenic fungus (Baur et al, 2019). Altogether, these results suggest that BTM female moths are not influenced by the amount of intact leaves and probably not either by their chemical quality when choosing the host plant, perhaps because of their strong ability to develop on toxic plants.…”
Section: Prior Herbivory Had No Effect Btm Oviposition Choicementioning
confidence: 86%
“…Even if prior herbivory induced the production of chemical defenses, it is possible they this did not exert any particular pressure upon females for choosing undefended leaves or plants on which to oviposit, as their offspring would have been able to cope with it. Last, BTM larvae proved to be unable to distinguish between box tree leaves infected or not by the box rust Puccinia buxi , while their growth is reduced in the presence of the pathogenic fungus (Baur et al, 2019). Altogether, these results suggest that BTM female moths are not influenced by the amount of intact leaves and probably not either by their chemical quality when choosing the host plant, perhaps because of their strong ability to develop on toxic plants.…”
Section: Discussionmentioning
confidence: 99%